The Moderating Role Of Work Motivation In The Relationship Between Competencies, Individual Characteristics, And Work Environment On Employee Performance - Nandyo Dwi Kendy; Suwarno Suwarno; RD kusumanto; Muhammad Yusuf (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of competence, individual characteristics, and work environment on employee performance, with work motivation as a moderating variable at BKPSDM Musi Rawas Regency. The study population amounted to 48 employees, and all were sampled through a saturated sampling technique. Data were collected through questionnaires that included independent variables (competence, individual characteristics, work environment), dependent variables (employee performance), and moderating variables (work motivation). The results showed that the three independent variables had a significant positive effect on employee performance. In addition, work motivation proved to moderate the relationship significantly. This finding indicates that optimal performance can be achieved through adequate competence, strong individual character, a conducive work environment, and high work motivation. The practical implications of these results encourage strengthening employee training, individual character mapping, work environment improvement, and motivation enhancement strategies. Theoretically, this research strengthens the interactional model in the study of public sector work behavior and contributes to the development of human resource management theory in the context of local government bureaucracy in Indonesia.